Mental Health Applications for Primary and Secondary Prevention of Common Mental Disorders: Attitudes of German Employees - Michaelis, Martina; Burgess, Stephanie; Junne, Florian; Rothermund, Eva; Gündel, Harald; Zipfel, Stephan; Wolf, Markus; Rieger, Monika A. (Frontiers in Psychiatry, 2021)
Background: Mental health applications (apps) in the internet and on mobile phones for the prevention and treatment of common mental disorders (CMDs) are on the rise, and are effective under certain circumstances in a range of conditions such as depression. Objective: There not sufficient evidence of benefits and barriers especially for mobile phone apps and for programs in the area of primary prevention. Studies on the acceptance of potential users of mental health apps yielded mixed outcomes. In large survey in 2016 we investigated the attitudes of employees towards mental health apps and various traditional mental health services. Our main research question in this contribution focuses on the acceptance of apps compared to other measures and the moderating influence of individual characteristics. Methods: The standardized survey was completed by members of an online access panel with different job types. A set of 33 self-developed items, including three questions on e-health, captured the perceived relevance of prevention at A) occupational, B) individual, and C) societal levels. On the basis of exploratory factor analysis, mean scores for mapping seven (sub)dimensions were constructed and compared using the Wilcoxon test. The influence of potential predictors was analyzed in linear regression models. Results: The data of 610 respondents were evaluated (response rate 75%). Support from mental health applications was rated significantly less important than all other dimensions at the levels A) to C). Respondents were more likely to use mental health apps if they felt literate with electronic devices, perceived a high relevance of work-related demands as causal factors for CMDs, stated they would be ashamed of having a CMD, and would be willing to begin psychotherapy if recommended Discussion and Conclusions: The results confirm the critical attitudes of potential mental health app users found in other studies. Since users with a negative attitude towards e-health might have a higher risk for dropout and non-adherence as well as lower intervention effects, well-designed educational strategies should be carried out beforehand.